Health scheduler : a web based booking system for health care services - Haukur Pálmason (2004)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri This report details the work performed as a final year project at the University of Akureyri during the school year 2003 to 2004. The project involved designing and writing a web based booking application for health care services in Iceland. In order to complete this task, detailed analysis of the Icelandic health care system and the booking procedure today was undertaken along with an extensive examination of the available web application techniques. After this research a simple web based booking system was built using a combination of advanced web technologies such as XML data representation, XSLT transformations and JDOM document model, along with proven techniques such as Java servlets. The initial version of this system, although not completed, proves that this combination of technologies is a powerful tool for today’s web application developer.